Factors Limiting Small-Scale Farmers’ Access and Use of Tractors for Agricultural Mechanization in Abuja, North Central Zone, Nigeria - Julius, Ajah (European Journal of Sustainable Development, 2014)
The importance of tractor and its implements in agricultural mechanization necessitated this study. The main objective is to identify factors limiting small-scale farmers’ access and use of tractors for farm mechanization in Abuja, Nigeria. To effectively cover the study area, a simple random technique was adopted for sample selection while semi-structured questionnaires were used for data collection. A total of 337 farmers were randomly selected from four local government areas (Kule, Kwali, Abaji, Gwagwalada) and used for the study. Data were analyzed using descriptive statistics. Results indicated that the major factors limiting the farmers from using tractors to work on their farms were high cost of tractor hiring services (64.09%) and inadequate sources of hiring points (19.29%) resulting in poor access to tractors and its implements. The farmers that hired tractors spent an average of N11,543 on land tillage alone hence majority (49.85%) of them adopted local implements like hoes, spades and shovels for land tillage while 10.39% planted without land tillage (zero tillage). In addition to land tillage, majority of the farmers (62.31%) indicated that, they also hired tractors for the transportation of their farm produce. Private ownership (NGO, Cooperative societies and private individuals) were the major (67.95%) sources of tractor for hiring while only 13.65% of the farmers accessed government- owned tractors. Based on the findings, the paper recommended that more tractor hiring points should be established in the study area and, in addition, the cost of hiring tractor should be regulated by government in order to encourage farm mechanization. Key words: Cost of tractor hiring, land tillage operation, transportation of farm produce, sources of tractor hiring